Examining healthy lifestyle behaviours of academic personnel working at a university (sample of Gaziantep University) - Kadir Tıryakı; Ugur Abakay (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to examine healthy lifestyle behaviours of academic personnel working in a university in Turkey and determine the relationships between healthy lifestyle behaviours and demographic characteristics. For that purpose, the 376 participants participated voluntarily to the study. Personal information form, and Health Promoting Lifestyle Profile II which was developed by Walker et al. were used in the study. Descriptive statistics, independent simple t test and One Way ANOVA were used to analyze the data, and for all data, level of significance was determined to be 0.05. As a result of this study, the female personnel was more successful than man personnel in sub-dimensions of physical activity and stress management. Also, the academic personnel engaged in regular physical activity had healthier lifestyle behaviours than others in all sub-dimensions.